Hubungan Antara Pengetahuan Tentang Operasi Katarak dan Tingkat Ekonomi Penderita Katarak dengan Sikap Tentang Operasi Katarak Pada Penderita Katarak Lanjut Usia di Wilayah Kerja Puskesmas Sukoharjo - Setiawan, Bayu, Agus Sudaryanto, S.Kep., Ns., M.Kes, Agustaria Budinugroho S. kep., Ns (2013)
Cataract is still a predominant disease of the eye and the most important cause of blindness.. Cataract surgery is a treatment in order to condition the better eye sight. Knowledge, level of economic factors can affect elderly attitude of cataract surgery. Objective aim to know relationship between knowledge of surgery and level economic of cataract patients with attitude of surgery cataract of elderly patients in public health service of Sukoharjo. This research method is descriptive research. Kind of research is quantitative research. Research design using pieces of cross sectional survey. sample research are 40 elderly aged 60 years and over who are visually impaired with cataracts. Takin sampling is using proportional random sampling Instrument in the form of a questionnaire study of knowledge and attitudes that have been tested for validity and reliability. Data analysis is using nonparametric Fisher-Exact test. Results research that 18 respondents (45%) with a high knowledge about cataract surgery, 22 respondents (55%) with less category. There are 16 respondents (40%) with high economic level, 24 respondents (60%) with low economic level. There are 17 respondents (42,5%) with a good attitude, 23 respondents (57,5%) with a bad attitude. Results of the statistical test Fisher exact between knowledge and attitudes about elderly cataract surgery obtained values obtained with p = 0.031. Results of the statistical test Fisher Exact level of economic relations and attitudes about the elderly cataract surgery values obtained with p = 0.013. The conclusion of this research is there is a relationship between knowledge of surgery with elderly attitude. there is relationship between level economic of cataract patients with attitude of surgery cataract of elderly patients in Public Health Service of Sukoharjo.